L-cysteine functionalized gold nanoparticles for Arsenic detection in water - González, Edgar E.; Acuña, Yesid A.; Quiroz, Ana M. (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
Experimental results of interactions of the amino acid L-cysteine (Cis) with gold nanoparticles (AuNPs) and gold nanoparticles functionalized with Cis (AuNPs+Cis) when As3+ ions are incorporated into the solution; all those processes are reported in this paper. In the aggregation processes, the role of the Cis concentration in the functionalization of the AuNPs is evaluated, in addition to the size of the nanoparticles when the ionic agent of interest is incorporated into the solution. The results show a sensitive dependence on the aggregation of the AuNPs+Cis nanoprobes as a function of their size, with a record of greater sensitivity for larger diameter nanoparticles. It is observed that the concentration of Cis in the functionalization process is a necessary condition for the programming of the stability of the nanoprobes, an essential aspect to configure a stable mode for the detection of the ionic agent. Therefore, these results allow us to establish useful criteria to design of colorimetric sensors to detect of heavy metals in contaminated water.